2008
DOI: 10.1016/s0079-6123(08)00403-2
|View full text |Cite
|
Sign up to set email alerts
|

The parvocellular vasopressinergic system and responsiveness of the hypothalamic pituitary adrenal axis during chronic stress

Abstract: Vasopressin (VP) secreted from parvocellular neurons of the hypothalamic paraventricular nucleus (PVN) stimulates pituitary ACTH secretion, through interaction with receptors of the V1b subtype (V1bR) in the pituitary corticotroph, mainly by potentiating the stimulatory effects of corticotrophin releasing hormone (CRH). Chronic stress paradigms associated with corticotroph hyperresponsiveness lead to preferential expression of hypothalamic VP over CRH and upregulation of pituitary V1bR, suggesting that VP has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 75 publications
6
92
1
11
Order By: Relevance
“…The involvement of neurohypophysial hormones and other neuroendocrine hormones in the regulation of corticotropic functions in fishes has been known, including the AVT and CRH/isotocin actions on ACTH secretion from pituitary of goldfish and rainbow trout (Baker et al, 1996;Fryer et al, 1985;Pierson et al, 1996), AVT and thyrotropin releasing hormone (TRH) actions on ACTH release in goldfish (Fryer et al, 1985;Lederis et al, 1994) and gilthead sea bream (Rotllant et al, 2000). The participation of the neurohypophysial hormones in direct stimulation of corticosteroid has been reported in amphibians (Larcher et al, 1992a) and mammals (Aguilera et al, 2008), indicating that the interplay between different hormonal axes or endocrine factors is widely present in vertebrates, including fishes, as summarized by Bernier and Klaren (2009). In a study using frogs, the stimulatory effect of AVT on corticosteroid secretion was found to be mediated through activation of receptors related to the mammalian V2 and/or OXT receptors in the interrenal tissues, which are positively coupled to phophoinositide-specific phospholipase C (Larcher et al, 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of neurohypophysial hormones and other neuroendocrine hormones in the regulation of corticotropic functions in fishes has been known, including the AVT and CRH/isotocin actions on ACTH secretion from pituitary of goldfish and rainbow trout (Baker et al, 1996;Fryer et al, 1985;Pierson et al, 1996), AVT and thyrotropin releasing hormone (TRH) actions on ACTH release in goldfish (Fryer et al, 1985;Lederis et al, 1994) and gilthead sea bream (Rotllant et al, 2000). The participation of the neurohypophysial hormones in direct stimulation of corticosteroid has been reported in amphibians (Larcher et al, 1992a) and mammals (Aguilera et al, 2008), indicating that the interplay between different hormonal axes or endocrine factors is widely present in vertebrates, including fishes, as summarized by Bernier and Klaren (2009). In a study using frogs, the stimulatory effect of AVT on corticosteroid secretion was found to be mediated through activation of receptors related to the mammalian V2 and/or OXT receptors in the interrenal tissues, which are positively coupled to phophoinositide-specific phospholipase C (Larcher et al, 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…Intracisternal lysine vasopressin (LVP) induced a dose-related decrease in BP and did not change HR (506). Fragments of AVP, AVP(1-6) and AVP (7)(8)(9), inhibited the pressor response caused by electrical stimulation of the mesencephalic reticular formation (521). AVP administration into the lateral ventricle increased BP in mice, and this BP increase was blocked by a selective V1a receptor antagonist and blunted in V1aR-KO mice (382).…”
Section: V2mentioning
confidence: 99%
“…For the control of ACTH secretion, CRH and AVP act synergistically on specialized cells, the corticotrophs, in the anterior pituitary gland (9,77,165,177,502). Although early studies proposed that AVP was the hypothalamic corticotrophin-releasing factor (331), after isolation of CRH from ovine hypothalami (515), this CRH peptide and its rodent and human counterparts proved to be a more powerful ACTH secretagogue than AVP, and it has since been shown to play a major role in the regulation of the HPA axis (7).…”
Section: The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…However, according to others [8][9][10], ACTH response to stress is dependent on the interaction of both, CRH and VP secretion. VP may act as an important modulator of ACTH responses to stress by potentiating the stimulatory effect of its major regulator, CRH [9,11,12]. According to Aguilera and RabadanDiehl [13], parvocellular VP expression and secretion may be independent on the osmotic status, being increased during stress in order to potentiate ACTH release.…”
Section: Introductionmentioning
confidence: 99%